IMPLEMENTATION OF THE LASERKU PRIORITY PROGRAM IN IMPROVING COMMUNITY HEALTH AND WELFARE - Efendi, Yuhnorur (Airlangga Development Journal, 2025)
Health is the main focus of the Lamongan Regent's priority programs as stated in the 2021-2026 RPJMD. One of the programs presented is LASERKU (Lamongan Sehat dan Sejahtera Dengan Kunjungan Rumah) ) where the main targets are less prosperous people who experience chronic diseases, congenital diseases, the elderly, malnutrition or stunting and mental health problems and people who have not been registered in JKN-PBI. This research aims to analyze collaboration in the implementation of the LASERKU (Lamongan Sehat dan Sejahtera Dengan Kunjungan Rumah)) program policy. This study uses a qualitative research approach with an interactive analysis model. This study found that implementation and collaboration resulted in the effectiveness of the LASERKU Priority Program in Lamongan Regency, thereby achieving several successes in improving community health and welfare.